Charbonneau e suas contribuições nos meios escolares: produção e circulação de saberes pedagógicos no período de 1959 a 1987: Charbonneau and its contributions in school environments: production and circulation of pedagogical knowledge from 1959 to 1987 (Revista Cocar, 2021)
Este artigo analisa o ideário pedagógico do Padre Paul-Eugène Charbonneau, a partir de prescrições de leituras de obras do educador cristão, situados no âmbito da História Cultural em torno da pedagogia católica. O objetivo do trabalho, é discutir a trajetória intelectual, bem como a aceitação de seus ideais escolares que passaram por diferentes estratégias de produção, apropriação e circulação. A pesquisa é bibliográfica e documental. Este trabalho considera a produção de Charbonneau, pautada num modelo de educação preventiva, que circulou na sociedade brasileira entre os anos de 1959 e 1987. Os livros e revistas estabelecem reflexões desse modelo pedagógico necessário às práticas, às representações e às apropriações (CERTEAU, 1982; CHARTIER, 1998). A análise considera, ainda, as narrativas escolares para o campo religioso como objeto da cultura escolar (BOURDIEU, 2005). Palavras-chave: História da Educação; Circulação de Saberes Pedagógicos; Pedagogia Católica. AbstractThis article¹ analyzes the pedagogical ideology of Father Paul-Eugène Charbonneau, based on reading prescriptions of works by the Christian educator, located in the scope of Cultural History around Catholic pedagogy. The objective of the work is to discuss the intellectual trajectory, as well as the acceptance of their school ideals that went through different production, appropriation and circulation strategies. The research is bibliographical and documentary. This work considers Charbonneau's production, based on a preventive education model, which circulated in Brazilian society between 1959 and 1987. Books and magazines establish reflections on this pedagogical model necessary for practices, representations and appropriations (CERTEAU, 1982; CHARTIER, 1998). The analysis also considers school narratives for the religious field as an object of school culture (BOURDIEU, 2005).Keywords: History of Education; Circulation of Pedagogical Knowledge; Catholic Pedagogy.